2014
DOI: 10.1111/jog.12319
|View full text |Cite
|
Sign up to set email alerts
|

Myo‐inositol modulates insulin and luteinizing hormone secretion in normal weight patients with polycystic ovary syndrome

Abstract: MYO administration positively modulates insulin sensitivity in non-obese PCOS patients without compensatory hyperinsulinemia, improving hormonal parameters. The presence of bromelin in the formulation modulated the pro-inflammatory state that characterizes PCOS, independently of BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 41 publications
1
26
0
1
Order By: Relevance
“…Moreover, this treatment improved the glucose tolerance and other metabolic profiles of these women (Costantino et al, 2009[13]). Similar results were reported when the effects of myo-inositol (3 g/d) on hormonal profiles and insulin response during an oral glucose tolerance test (OGTT) in normal weight PCOS patients were analyzed (Genazzani et al, 2014[27]). Genazzani et al (2008[25]) reported that myo-inositol supplementation (2 g/d) plus folic acid (200 µg/ d) was effective in the amelioration of plasma luteinizing hormone (LH), Prolactin (PRL), and testosterone levels in overweight PCOS patient after 12 weeks consumption, probably through the reduction in plasma insulin concentration (Genazzani et al, 2008[25]).…”
Section: Nutrients and Pcossupporting
confidence: 70%
See 1 more Smart Citation
“…Moreover, this treatment improved the glucose tolerance and other metabolic profiles of these women (Costantino et al, 2009[13]). Similar results were reported when the effects of myo-inositol (3 g/d) on hormonal profiles and insulin response during an oral glucose tolerance test (OGTT) in normal weight PCOS patients were analyzed (Genazzani et al, 2014[27]). Genazzani et al (2008[25]) reported that myo-inositol supplementation (2 g/d) plus folic acid (200 µg/ d) was effective in the amelioration of plasma luteinizing hormone (LH), Prolactin (PRL), and testosterone levels in overweight PCOS patient after 12 weeks consumption, probably through the reduction in plasma insulin concentration (Genazzani et al, 2008[25]).…”
Section: Nutrients and Pcossupporting
confidence: 70%
“…1) (References in Table 1: Costantino et al, 2009[13]; Genazzani et al, 2014[27]; Genazzani et al, 2008[25]; Nestler et al, 1999[48]; Genazzani et al, 2014[26]; Laganà et al, 2015[39]; Nordio and Proietti, 2012[49]; Pizzo et al, 2014[60]).…”
Section: Nutrients and Pcosmentioning
confidence: 99%
“…MYO-INS could be found both in free form and as component of the membrane phosphoinositides into the cells [ 4 ]. Phosphatidyl-myo-inositol is the precursor of phosphatidyl-Ins phosphate and phosphatidyl-Ins bisphosphate (PIP2) whose hydrolysis results in Ins trisphosphate (Ins-1,4,5P3, InsP3) that plays the role of second messenger taking part in the activities of several hormones such as follicle-stimulating hormone (FSH) and insulin [ 4 , 5 ]. Moreover, InsP3 binds the membrane receptors of mitochondria and the endoplasmic reticulum, leading to an increase in calcium influx into the cytosol, which activates protein kinase C and mediates cellular responses [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphoglycans formed by DChiro-Inositol seem to play a relevant role in insulin signaling transduction and seems to be more effective in partially restoring insulin sensitivity and glycogen synthesis than phosphoglycan incorporating Myo-Inositol [25]. Accumulating evidence suggests that Myo-Inositol could play a key role in improving hormonal and metabolic homeostasis in PCOS [26][27][28][29][30][31], assisted reproductive technology (ART) [32][33][34][35], and even in Gestational Diabetes Mellitus (GDM) [36][37][38][39]. Nevertheless, in PCOS patients, Myo-Inositol seems to have the most marked effect on the metabolic profile, whereas D-Chiro-Inositol reduces hyperandrogenism better [40].…”
Section: Introductionmentioning
confidence: 97%